Relasi Konseptual Oposisi Makna Sumbangan Korporasi Pada Partai Politik Dalam Semiotic Square - Tashya Panji Nugraha (Jurnal Hukum IUS QUIA IUSTUM, 2019)
Legal language can be utilised as a means to manipulate interests. A specific approach is needed to identify the potential distortion behind the text of positive legal norms. This study applies a legal semiotics approach. Through the semiotic square model, the potential for distortion at the conceptual level can be brought up to the surface. The result of the interpretation shows that Article 35 paragraph (1) letter c of Law Number 2 of 2011 on Political Parties has the potential to be a means for corporations to infiltrate their interests. The opposing conceptual relations of meanings that can come up include: the corporate contributions to political parties which can be used as a means to influence the economic policies that would only favour the corporations; demanding the regulations that only protect, facilitate and benefit corporate activities; as well as investment field for the corporations to request the licensing and project or tender facilities. In the end, political parties do not have the sovereignty, independency and integrity.